Emergence and evolution of epizootic hemorrhagic disease virus in the Mediterranean region: spatio-temporal dynamics and epidemiological insights - Marwa Arbi; Marwa Arbi; Emna Harigua-Souiai; Mariem Hanachi; Imen Larbi; Melek Chaouch; Dorra Rjaibi; Mohamed Fethi Diouani; Alia Benkahla; Oussema Souiai; Oussema Souiai (Frontiers in Veterinary Science)
BackgroundEpizootic Hemorrhagic Disease Virus (EHDV) is an arbovirus, transmitted to wild and domestic ruminants through Culicoides biting midges. Since 2006, high morbidity and mortality cases of EHDV have been reported among cattle and deer populations in several Mediterranean countries. The temporal and geographic origins of these incursions remained unclear. In this study, we aimed to investigate the evolutionary history of EHDV in the Mediterranean region and highlight the epidemiological features of viruses in relationship with genetic diversity and viral ecology.MethodsWe extracted from GenBank the EHDV VP2 and VP5 segments isolated in the mediterranean region during the period 2006 to 2023 and blasted them to obtain a final dataset of 68 and 91 nucleotide sequences. Using these datasets, we conducted a Bayesian phylodynamic analysis, which inferred discrete models of “geographic origin,” “Serotype” and “Host” by employing the BEAST package.ResultsRSPP and TMRCA analyses showed that the Mediterranean EHDV has as ancestral root the North America strains that circulated in the 17th century. Our study suggested that the first EHDV incursions in the Mediterranean region started in France and Tunisia during the 1800s. The latter countries were epicenters of EHDV in the region. Significant transition routes (BF>3) were detected revealing virus transmission between North African and European countries. Serotype model study revealed VP5 multiple inter-serotype events involving serotypes 1, 2, 6, 7, and 8 with high statistical support (BF>100). Significant virus transmission was detected for Cattle-deer and Culicoides-Cattle transition routes.ConclusionThe virus transmission was intense between North African and European countries of the Mediterranean region. EHDV spread in this region seems to be influenced mainly by vector/host distribution and abundance, ruminants' trade and prevailing winds.